A Multicenter, Randomized, Controlled Phase IIb Trial of Avoidance of Hyperoxemia During Cardiopulmonary Bypass. Issue 2 (April 2017) - McGuinness, S. P.; Parke, R. L.; Drummond, K.; Willcox, T.; Bailey, M.; Kruger, C.; Baker, M.; Cowdrey, K. A.; Gilder, E.; McCarthy, L.; Painter, T.
Abstract : (Abstracted from Anesthesiology, 125(3):465–473, 2016) More than 1.25 million undergo cardiopulmonary bypass (CPB) annually. The purpose of this multicenter, randomized controlled trial was to assess whether avoiding arterial hyperoxemia would reduce the severity of the multiorgan dysfunction (MOD) in those undergoing CPB.